Living it up with a Live Programming Language - McDirmid, Sean (OOPSLA Onward!, 2007)
A dynamic language promotes ease of use through ﬂexible typing, a focus on high-level programming, and by streamlining the edit-compile-debug cycle. Live languages go beyond dynamic languages with more ease of use features. A live language supports live programming that provides programmers with responsive and continuous feedback about how their edits affect program execution. A live language is also based on high-level constructs such as declarative rules so that programmers can write less code. A live language could also provide programmers with responsive semantic feedback to enable time-saving services such as code completion. This paper describes the design of a textual live language that is based on reactive data-ﬂow values known as signals and dynamic inheritance. Our language, SuperGlue, supports live programming with responsive semantic feedback, which we demonstrate with a working prototype.
The "live" version of this paper is best viewed in Acrobat Reader with Quicktime installed.